The Dissertation Journey: A Practical Guide to Planning, Writing, and Defending Your Dissertation - Metcalfe, Laura Schaffer (Journal of Interdisciplinary Studies in Education, 2019)
This book is practical, guided, and forthright on what is needed to get started with the dissertation process. Its format is simple to and easy to read as it is broken down into chapters with information in each chapter outlined on its own page. This simple and uncomplicated format is a pleasure to read and it will not overwhelm doctoral students who are looking to move into this process of their academic careers. I strongly believe that authors Roberts and Hyatt have successfully accomplished their stated purpose for this text.